Brewer v. Williams, Massiah and Miranda: What Is 'Interrogation'? When Does It Matter? - Kamisar, Yale (1978)
On Christmas Eve, 1968, a ten-year-old girl, Pamela Powers, disappeared while with her family in Des Moines, Iowa.2 Defendant Williams, an escapee from a mental institution and a deeply religious person, 3 was suspected of murdering her, and a warrant was issued for his arrest.4 Williams telephoned a Des Moines lawyer, McKnight, and on his advice surrendered himself to the Davenport, Iowa, police.5 Captain Learning and another Des Moines police officer arranged to drive the 160 miles to Davenport, pick up Williams, and return him directly to Des Moines. 6 Both the trial court 7 and the federal district court8 found that defense attorney McKnight and the Des Moines police agreed that Williams would not be questioned until after he returned to Des Moines and conferred with his lawyer.9 Before being driven back to Des Moines, Williams was advised of his rights many times-by McKnight over the phone, by Kelly (his Davenport attorney), by the Davenport judge who arraigned him on the warrant, by a Davenport police officer, and by Leaming himself.10 More important, Williams asserted his rights many times. He retained counsel in both Des Moines I and Davenport. 12 He requested and was granted a private meeting with the Davenport judge.' 3 After Leaming arrived and advised him of his rights, Williams requested and was granted two private meetings with attorney Kelly.' 4 Kelly, furthermore, told Leaming that Williams was not to be questioned until he met with McKnight. 15 Kelly also requested, but was refused, permission to ride back with his client.' 6 Finally, on the trip back, Williams told Leaming several times that he would tell him the whole story after he saw McKnight in Des Moines.17 The Court's reading of the record, and the best reading, 18 is that not long after Captain Leaming and his prisoner left Davenport and entered the freeway, the captain delivered his now famous Christian burial speech. 19 Although there are two significantly different versions of the speech, 20 I shall proceed, as did the Supreme Court and lower federal courts, on the assumption that there was only one.21 According to the Court's opinion, the detective addressed Williams as Reverend and continued: I want to give you something to think about while we're traveling down the road .. . .Number one, I want you to observe the weather conditions, it's raining, it's sleeting, it's freezing, driving is very treacherous, visibility is poor, it's going to be dark early this evening. They are predicting several inches of snow for tonight, and I feel that you yourself are the only person that knows where this little girl's body is, that you yourself have only been there once, and if you get a snow on top of it you yourself may be unable to find it. And, since we will be going right past the area on the way into Des Moines, I feel that we could stop and locate the body, that the parents of this little girl should be entitled to a Christian burial for the little girl who was snatched away from them on Christmas [E]ve and murdered. And I feel we should stop and locate it on the way in rather than waiting until morning and trying to come back out after a snow storm and possibly not being able to find it at all. Williams asked Detective Leaming why he thought their route to Des Moines would be taking them past the girl's body, and Leaming responded that he knew the body was in the area of Mitchellville-a town they would be passing on the way to Des Moines. . . . Leaming then stated: I do not want you to answer me. I don't want to discuss it any further. Just think about it as we're riding down the road. 2